Differential effects of lung inflammation on insulin resistance in humans and mice. Issue 8 (4th February 2022) - Karlina, Ruth; Flexeder, Claudia; Musiol, Stephanie; Bhattacharyya, Madhumita; Schneider, Evelyn; Altun, Irem; Gschwendtner, Silvia; Neumann, Avidan U.; Nano, Jana; Schloter, Michael; Peters, Annette; Schulz, Holger; et al.
Abstract: Background: The rates of obesity, its associated diseases, and allergies are raising at alarming rates in most countries. House dust mites (HDM) are highly allergenic and exposure often associates with an urban sedentary indoor lifestyle, also resulting in obesity. The aim of this study was to investigate the epidemiological association and physiological impact of lung inflammation on obesity and glucose homeostasis. Methods: Epidemiological data from 2207 adults of the population‐based KORA FF4 cohort were used to test associations between asthma and rhinitis with metrics of body weight and insulin sensitivity. To obtain functional insights, C57BL/6J mice were intranasally sensitized and challenged with HDM and simultaneously fed with either low‐fat or high‐fat diet for 12 weeks followed by a detailed metabolic and biochemical phenotyping of the lung, liver, and adipose tissues. Results: We found a direct association of asthma with insulin resistance but not body weight in humans. In mice, co‐development of obesity and HDM‐induced lung inflammation attenuated inflammation in lung and perigonadal fat, with little impact on body weight, but small shifts in the composition of gut microbiota. Exposure to HDM improved glucose tolerance, reduced hepatosteatosis, and increased energy expenditure and basal metabolic rate. These effects associate with increased activity of thermogenic adipose tissues independent of uncoupling protein 1. Conclusions: Asthma associates with insulin resistance in humans, but HDM challenge results in opposing effects on glucose homeostasis in mice due to increased energy expenditure, reduced adipose inflammation, and hepatosteatosis. Abstract : This study investigates the epidemiological association and physiological impact of lung inflammation on obesity and glucose homeostasis. Asthma is associated with increased insulin resistance independently of a body fat mass. HDM‐induced lung inflammation increases energy expenditure, decreases adipose tissue inflammation, and hepatosteatosis, resulting in improved glucose tolerance in high‐fat diet‐induced obese mice.Abbreviations: CI, confidence interval, HDM, house dust mite; HFD, high‐fat diet; HOMA‐IR, homeostasis model assessment‐estimated insulin resistance; KORA‐FF4, Cooperative Health Research in the Augsburg Region; LFD, low‐fat diet; PBS, phosphate‐buffered saline; WHR, waist‐to‐hip ratio